Perancangan Arsitektur Sistem Distribusi Pupuk Bersubsidi dengan Teknologi Blockchain - Eko Purwanto Aribowo; Andi Wahju Rahardjo Emanuel (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
Digitalizing subsidized fertilizers distribution control is one of the government's efforts to increase program effectiveness. Information technology on Kartu Tani can record various transaction records, such as the remaining subsidized fertilizer quota for each farmer and purchase records. However, using Kartu Tani is still not optimal because some problems apply to this technology. The problems that often occur are data recording errors, using cards that do not fit their purpose and other distribution problems. This research aimed at reducing system weaknesses in the farmer card program has been carried out before, but the application of Blockchain technology in the distribution of subsidized fertilizers has not been widely discussed. This research will propose using Blockchain with the Hyperledger Fabric Framework to design a subsidized fertilizer distribution information system. Blockchain technology was chosen because it has suitable properties to overcome problems, including decentralization and immutability. These characteristics can be developed to build a transparent and integrity information system. The output of this study is an architectural design of subsidized fertilizer distribution that farmers easily accept.